KARYA TARI GRAFITY TOILET: FENOMENA SOSIAL PENYALAHGUNAAN RUANG PUBLIK - Fitra Airiansyah (Universitas Andalas, 2018)
The Toilet graph is visualized on the basis of an interpretation of the Creator's creative ideas. Imagination finally gave birth to new forms in the show. The creation of Grafity Toilet dance work is inspired by social phenomena by focusing on the misuse of public toilets, public toilets are not just places of biological need but also functioned as negative ones such as nasty places, transactions of forbidden goods, and murder. The cultivation method consists of three stages: exploration, improvisation and formation. The structure of Gravity Toilet dance works is divided into three sections with several scenes depicting some activities and actions of toilet abuse. Keywords: grafity, toilet, social phenomenon